INVESTIGATION OF VOLT-CAPACITY CHARACTERISTICS OF SI-PHOTODETECTORS (World Economics and Finance Bulletin, 2022)
The behavior of the electrophysical characteristics of silicon Si-photodetectors before and after ultrasonic treatment is studied. It is shown that due to the acoustically stimulated diffusion of phosphorus at a low temperature (T»300K), the p-Si base is compensated, which becomes more high-resistance, which leads to an increase in the drop in the applied bias voltage Vb on the depleted layer Wd and an increase in the electric field strength in it. As a result of these processes, an increase in the magnitude of the short circuit current is observed, which causes an increase in the open circuit voltage and the efficiency of such a diffusion Si-n-p structure operating in the photoconversion mode.
Keywords: Ultrasound; Si radiation receivers; Si-photodetectors